PET imaging of somatostatin receptors using (68GA)DOTA-D-Phe1-Tyr3-octreotide: first results in patients with meningiomas : brief communications - Henze, Marcus; Hipp, Peter; Becker, Dirk Wolfram; Doll, Josef; Mäcke, Helmut R.; Debus, Jürgen; Haberkorn, Uwe (Journal of nuclear medicine, 2001)
Imaging of somatostatin receptors (SSTRs) using [111In]diethylenetriaminepentaacetic-acid-octreotide (DTPAOC) has proven to be helpful in the differentiation of meningiomas, neurinomas or neurofibromas, and metastases as well as in the follow-up of meningiomas. A drawback of the SPECT method is its limited sensitivity in detecting small meningiomas. Because of PET’s increased spatial resolution and its ability to absolutely quantify biodistribution, a PET tracer for SSTR imaging would be desirable. Methods: 1,4,7,10-tetraazacyclododecane-N,N′,N″,N‴-tetraacetic-acid-d-Phe1-Tyr3-octreotide (DOTATOC) was labeled using the positron-emitting generator nuclide 68Ga. We acquired dynamic PET images over 120 min after intravenous injection of 175 MBq [68Ga]DOTATOC in 3 patients suffering from 8 meningiomas (WHO I°; 7- to 25-mm diameter). Patients’ heads had been fixed using individually shaped fiber masks equipped with an external stereotactic localizer system to match PET, CT, and MRI datasets. Results: [68Ga]DOTATOC was rapidly cleared from the blood (half-life α, 3.5 min; half-life β, 63 min). Standardized uptake values (SUVs) of meningiomas increased immediately after injection and reached a plateau 60-120 min after injection (mean SUV, 10.6). No tracer could be found in the surrounding healthy brain tissue. All meningiomas (even the 3 smallest [7- to 8-mm diameter]) showed high tracer uptake and could be visualized clearly. Tracer boundaries showed a good correspondence with the matched CT and MRI images. PET provided valuable additional information regarding the extent of meningiomas located beneath osseous structures, especially at the base of the skull. Conclusion: According to our initial experiences, [68Ga]DOTATOC seems to be a very promising new PET tracer for imaging SSTRs even in small meningiomas, offering excellent imaging properties and a very high tumor-to-background ratio.